Prevalence of Malaria at District Shaheed Benazirabad - Riaz Ahmed Qazi, Javaid Hussain Memon, Ameer Abbas, A. Rahim Solangi, Ailaz Ahmed Memon , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To evaluate the frequency of Malaria on the basis of two common species of malarial parasite at district (SBA) Shaheed Benazirabad. Study Design: Descriptive and experimental study. Place & Duration of study: This study was conducted at Diagnostic &. research laboratory in Pathology Department of Peoples University of Medical & Health Sciences Nawabshah, at (SBA) from April 2015 to September 2015. Material & Methods: Total 300 patients including 197 males.103females at their ages ranged between 3 and 71 years were selected. History of fever with or without associated symptoms and clinical examination including anemia as well as splenomegaly were noted and all the blood samples were sent to the laboratory for complete blood analysis, examination of peripheral blood smears and immunochromatography test (ICT) to identify common species of malarial parasites. Data were analyzed by using statistical package for social sciences (SPSS) version 17.0. Results: The mean age of total patients was 37+34 years and male to female ratio was 1.9:1. The frequency of P. vivax was founded in 230 ( 76.6%)patients and P. falciparum in 70 (23.4%) patients by direct microscopy of stained thick and thin peripheral blood smears. ICT Malaria test was positive in 103 (34.3%) patients with P.vivax malaria infection while this test was positive in 10 (3.3%) of cases with p. falciparum malaria infection and 1CT malaria is negative in 1S7 (62.4")/0) cases out of total 300 patients with malaria, Conclusion: The frequency of P vivax malaria is more common than the falciparum malaria needed early diagnosis. prevention and urgent treatment to reduce mortality rate due to severe complications,